Ureteral dilation recovery after intravesical reimplantation in children with primary obstructive megaureter - He, Yan; Wu, Xuemin; Xu, Yingrui; Liu, Zhaoquan; Du, Guoqiang; Wu, Xiangyu; Liu, Wei; Wu, Rongde (Frontiers in Pediatrics, 2023)
Background To observe the postoperative recovery following ureteral dilation in primary obstructive megaureter (POM) after ureteral implantation, and evaluate the risk factors affecting ureter diameter resolution. Materials and Methods A retrospective study was performed in patients with POM who underwent ureteral reimplantation using the Cohen procedure. Patient characteristics, perioperative parameters, and postoperative outcomes were also analysed. A widest ureteral diameter of <7 mm was defined as a normal shape and outcome. Survival time was defined as the time from surgery to ureteral dilation recovery or to the last follow-up. Results A total of 49 patients (54 ureters) were included in the analysis. The survival time ranged from 1 to 53 months. The shapes of a total of 47 (87.04%) megaureters recovered, and most (29/47) resolutions happened within 6 months after surgery. In the univariate analysis, bilateral ureterovesical reimplantation (p = 0.015), ureteral terminal tapering (p = 0.019), weight (p = 0.036), and age (p = 0.015) were associated with the recovery time of ureteral dilation. A delayed recovery of ureteral diameter was noted in bilateral reimplantation (HR = 0.336, p = 0.017) using multivariate Cox regression. Conclusions Ureteral dilation in POM mostly returned to normal within six postoperative months. Moreover, bilateral ureterovesical reimplantation is a risk factor for delayed postoperative recovery of ureter dilation in POM.